STRATEGI KEPOLISIAN NEGARA REPUBLIK INDONESIA (POLRI) DALAM MENANGANI PENYELUNDUPAN NARKOBA LINTAS BATAS DI WILAYAH RIAU TAHUN 2015-2016 - Simanjuntak, Christin Natalia; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain The Indonesian National Police (INP) strategies in countering the cross-border narcotics smuggling by a international narcotics syndicates from Malaysia that occurred in the Riau region. Ditreserse Narcotics of the Riau Regional Police stated that there was an increase in the number of narcotics cases in Riau in 2015 to 2016. In 2015, there were 1,137 cases. Later on, 2016 became 1.425 cases . In this research, the author uses the perspective of Neorealism that focuses on the structure of systems, unit interactions, continuity and system changes. To bridge between the problem and the hypothesis, the author uses the level of analysis of the nation-state. Furthermore, this research uses the Universe Defense Strategy Theory from I Wayan Mudita based on the universal state defense strategy on the Indonesian Defense White Paper. The Indonesian National Police in countering the cross-border narcotics smuggling in the Riau region uses the internal and external strategies. The internal strategies are in the form of pre-emptive, preventive and repressive actions carried out by the interdiction agency of Riau Province. Besides, the external strategy, INP collaborates with The Royal Malaysia Police. The research finds that INP has a strong commitment in countering the cross-border narcotics smuggling in order to achieve the condition of Indonesia without drugs.Keywords: Strategy, The Indonesian National Police (INP), Countering, Narcotics Smuggling, Riau Region